The age of decadence Britain 1880 to 1914 - Heffer, Simon 1960- (Windmill Books, 2018)
"The folk memory of Britain in the years before the Great War is of a powerful, contented, orderly and thriving country. She commanded a vast empire. She bestrode international commerce. Her citizens were living longer, profiting from civil liberties their grandparents only dreamt of, and enjoying an expanding range of comforts and pastimes. The mood of pride and self-confidence is familiar from Elgar's Pomp and Circumstance marches, newsreels of George V's coronation and the London's great Edwardian palaces. Yet things were very different below the surface. In 'The Age of Decadence' Simon Heffer exposes the contradictions of late-Victorian and Edwardian Britain"--Provided by publisher
Keywords: Geschichte 1880-1914; Großbritannien; Great Britain / History / Victoria, 1837-1901; Great Britain / History / Edward VII, 1901-1910; Great Britain / History / George V, 1910-1936; Great Britain / Social conditions / 19th century; Great Britain / Social conditions / 20th century; Social conditions; Great Britain; 1800-1999; History